Produção de esferoides a partir de células-tronco/estromais de tecido adiposo humano para fabricação de tecido ósseo in vitro - Kronemberger, Gabriela Soares (2018)
New bone formation is desirable in a variety of pathological settings, such as osteoporosis. Adipose derived stem/stromal cells (ASCs) are considered a promising cell source for the formation of this tissue in vitro through tissue engineering techniques. A new approach in the field of tissue engineering corresponds to the use of stem-cell spheroids as modular units for fabricate biological tissues in vitro. Thus, the aim of this work was to standardize an osteogenic induction model in vitro from spheroids of human ASCs produced by micromolded nonadhesive hydrogel. ASCs were isolated by mechanical dissociation from human lipoaspirate samples obtained according to the local research ethics committee. Two strategies for osteogenic differentiation induction were evaluated in ASCs spheroids produced by micromolded nonadhesive hydrogel. Spheroids maintained in culture medium without inducing factors were maintained as controls. Measurements of spheroid diameter were performed using phase contrast optical microscopy images. Spheroids induced by hrBMP-7 and by TGF-β3 presented a diameter mean of 370 μm and 450 μm respectively. The hrBMP-7 induced spheroids showed high cell viability (85%), quantified by 7-AAD exclusion detected by flow cytometry. The TGFβ3 induced spheroids also showed high cell viability throughout the weeks of culture, as assessed by commercial fluorescence kit. The TGF-β3-induced spheroids exhibited more calcium deposits than those induced by hrBMP-7, identified by alizarin red staining in histological sections. In both cases, X-ray microanalysis (EDX) showed the presence of calcium only in induced spheroids. The hrBMP-7 induced spheroids showed higher alkaline phosphatase mRNA expression (p = 0.0015) and lower TSP-1 expression (p = 0.00016) when compared to control spheroids. However, there was no difference in RUNX2 and Sox9 expression. The TGF-β3 induced spheroids had a higher composition of typical extracellular matrix components, such as collagen I, osteocalcin, osteopontin, biglycan and tenascin C by immunohistochemistry when compared to those induced by hrBMP-7. In addition, the mechanical resistance to compression of spheroids induced by TGF-β3 was higher when compared to spheroids induced by hrBMP-7 (mean of 360μN and 20μN, respectively). Therefore, it was possible to standardize an in vitro osteogenic induction model of human ASCs spheroids. It was also concluded that induction by TGF-β3 followed by induction with osteogenic medium is able to produce differentiated spheroids with greater efficiency of osteogenic differentiation than spheroids induced by hrBMP-7. In this work, it was possible to standardize a model of in vitro osteogenic induction of human ASCs spheroids, opening a new perspective for regenerative medicine.